2019
DOI: 10.1002/cppb.20092
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Cell Wall Monosaccharides and Nucleotide‐Sugars from Plants

Abstract: The cell wall is an intricate mesh largely composed of polysaccharides that vary in structure and abundance. Apart from cellulose biosynthesis, the assembly of matrix polysaccharides such as pectin and hemicellulose occur in the Golgi apparatus before being transported via vesicles to the cell wall. Matrix polysaccharides are biosynthesized from activated precursors or nucleotide sugars. The composition and assembly of the cell wall is an important aspect in plant development and plant biomass utilization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Based on this concept, we explored and compared the composition of the three Symbiodiniaceae cell surfaces. A multi-step approach, comprising both well-established [ 20 , 29 , 30 ] and innovative methods [ 31 ], was adopted to profile the cell surface of these Symbiodiniaceae. In this way, we created a list of potential molecular candidates, that we then strategically altered to investigate their role(s) during the first stages of symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this concept, we explored and compared the composition of the three Symbiodiniaceae cell surfaces. A multi-step approach, comprising both well-established [ 20 , 29 , 30 ] and innovative methods [ 31 ], was adopted to profile the cell surface of these Symbiodiniaceae. In this way, we created a list of potential molecular candidates, that we then strategically altered to investigate their role(s) during the first stages of symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Graphitized carbon as a stationary phase for the SPE of polar compounds has gained popularity [45]. In particular, nucleotide sugars can be successfully extracted with this method using an ion-pairing reagent as eluent [46][47][48]. Stationary phases with phenyl-boronate groups are uniquely suited to retain sugars with a cis-diol group (see Section 4), which can be used not only for the removal or enrichment of rNTs and rNs [49], but also for the extraction of brassinosteroids from Arabidopsis thaliana [50].…”
Section: Solid-phase Extractionmentioning
confidence: 99%
“…As mentioned above, the chromatographic separation of isobaric NTs is very important to avoid that metabolites of nearly identical mass are wrongly assigned and quantified, which could lead, for example, to confounding dGTP with adenosine triphosphate (ATP) [12] or IMP with AMP isotopes. Furthermore, several publications have shown that PCG-chromatography is able to separate nucleotide sugars [12,46,47].…”
Section: Chromatographic Separationmentioning
confidence: 99%
“…Monosaccharide analysis: Alcohol insoluble residue (AIR) was prepared, and pectin and hemicellulose fractions were extracted sequentially as previously described (Rautengarten et al, 2019). AIR (10-15 mg) obtained from dark-grown hypocotyls was extracted using 50 mM CDTA (pH 6.5), 50 mM Na2CO3, 1 M and 4 M KOH for 2 h at room temperature and 16 h at 4°C.…”
Section: Cell Wall Analysesmentioning
confidence: 99%
“…Total alcohol insoluble residue or corresponding cell wall fractions were hydrolyzed in 2 N trifluoroacetic acid (TFA) for 1 h at 120°C. High-Performance anion exchange chromatography (HPAEC) coupled with pulsed amperometric detection (PAD) was performed on an ICS 5000 device (Dionex) using a CarboPac PA20 (3 × 150 mm) anion-exchange column (Dionex) (Rautengarten et al, 2016).…”
Section: Cell Wall Analysesmentioning
confidence: 99%